Processes through Which Transformational Leaders Affect Employee Psychological Health. (February 2014) - Walsh, Megan; Dupré, Kathryne; Arnold, Kara A.
This study investigates the processes through which transformational leaders influence employee psychological health. The results indicate that employees' perceptions of justice of the organization and psychological empowerment mediate the positive relationship between transformational leadership and psychological health. This study supports the notion that transformational leadership influences individuals' perceptions of organizations, as well as individuals' perceptions of themselves, which ultimately has implications for individual well-being.